The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Elevated CO 2 Increases the Canopy Temperature of Mature Quercus robur (Pedunculate Oak) - William Hagan Brown; Emanuel Gloor; Ralph Fyfe; A. Rob MacKenzie; Nicholas J. Harper; Peter Ganderton; Kris Hart; Giulio Curioni; Susan Quick; Scott J. Davidson; Emily Yetton; Jen L. Diehl; et al. (Global Change Biology, 2025)
The canopy thermal response of natural forests to elevated CO 2 (eCO 2 ) is an understudied biophysical feedback in the global climate system. We investigated the effects of eCO 2 (150 μmol mol −1 above ambient) on canopy temperature ( T can ) dynamics of mature (> 175 years) Quercus robur (oak) at the Birmingham Institute for Forest Research Free Air CO 2 Enrichment (BIFoR‐FACE) facility in Staffordshire, England, during the growing seasons of 2021, 2022 and 2023. We employed long‐term, high‐frequency thermal infrared (TIR) imaging to measure T can . Our results show that daily maximum oak T can under eCO 2 was, on average, approximately 1.3°C higher than under ambient (aCO 2 ) conditions (21.5°C ± 4.4°C for aCO 2 vs. 22.8°C ± 5.2°C for eCO 2 oaks). Moreover, daily maximum T can –air temperature ( T air ) differences were significantly higher under eCO 2 , resulting from more frequent extreme temperature excursions. These differences appear primarily to be driven by reduced stomatal conductance under eCO 2 , which limits transpirational cooling and alters the surface energy balance. This effect was evident in the different relationship between T can – T air and vapour pressure deficit (VPD) for eCO 2 compared to aCO 2 , showing a reduction in transpirational cooling under high VPD. Also, CO 2 ‐induced leaf structural and anatomical modifications, such as increased leaf mass per area, may have enhanced solar radiation absorption, thereby enabling greater canopy warming under high radiation conditions. Thus, eCO 2 could likely cause a reduction in leaf transpiration in oaks, reducing its contribution to processes such as humidification of the lower atmosphere and precipitation in local and regional climates. Our findings highlight how high CO 2 conditions may intensify thermal stress in temperate forests, influencing water and carbon cycles and potentially impacting forest resilience. Furthermore, T can will be essential for refining global Earth system models, which often use T air as a proxy for T can , despite the latter's direct influence on carbon and hydrological cycles.

Modelling Cross-Shore Shoreline Change on Multiple Timescales and Their Interactions - Rob Schepper; Rafael Almar; Erwin Bergsma; Sierd de Vries; Ad Reniers; Mark Davidson; Kristen Splinter (Journal of Marine Science and Engineering, 2021)
In this paper, a new approach to model wave-driven, cross-shore shoreline change incorporating multiple timescales is introduced. As a base, we use the equilibrium shoreline prediction model ShoreFor that accounts for a single timescale only. High-resolution shoreline data collected at three distinctly different study sites is used to train the new data-driven model. In addition to the direct forcing approach used in most models, here two additional terms are introduced: a time-upscaling and a time-downscaling term. The upscaling term accounts for the persistent effect of short-term events, such as storms, on the shoreline position. The downscaling term accounts for the effect of long-term shoreline modulations, caused by, for example, climate variability, on shorter event impacts. The multi-timescale model shows improvement compared to the original ShoreFor model (a normalized mean square error improvement during validation of 18 to 59%) at the three contrasted sandy beaches. Moreover, it gains insight in the various timescales (storms to inter-annual) and reveals their interactions that cause shoreline change. We find that extreme forcing events have a persistent shoreline impact and cause 57–73% of the shoreline variability at the three sites. Moreover, long-term shoreline trends affect short-term forcing event impacts and determine 20–27% of the shoreline variability.

The Changing Role of ENGOs in Water Governance: Institutional Entrepreneurs? - Seanna L. Davidson; Rob C. de Loë (Environmental Management, 2016)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Quantifying the effect of soil compaction on three varieties of wheat (Triticum aestivum L.) using X-ray Micro Computed Tomography (CT) - Saoirse R. Tracy; Colin R. Black; Jeremy A. Roberts; Ann McNeill; Rob Davidson; Mark Tester; Marko Samec; Dean Korošak; Craig Sturrock; Sacha J. Mooney (Plant and Soil, 2012)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Report of The Site Selection Committee to the PAA Business Meeting Wednesday July 27, 1994 - Brian L. Rex; Joe Sieczka; Alexander Pavlista; Duane Preston; Pete Weingartner; Robert O’Keefe; Jonathon Whitworth; Chesley E. Smith; Rob Davidson; Gregory Porter; Dan Hane; Terry Work (American Journal of Potato Research, 1994)